2013 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--19845
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Visuohaptic Simulations for Conceptual Understanding in Electricity and Magnetism

Abstract: Lafayette. Magana's research interests are centered on the integration of cyberinfrastructure, computation, and computational tools and methods to: (a) leverage the understanding of complex phenomena in science and engineering and (b) support scientific inquiry learning and innovation. Specific efforts focus on studying cyberinfrastructure affordances and identifying how to incorporate advances from the learning sciences into authoring curriculum, assessment, and learning materials to appropriately support lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Previous work that has used visual cues and haptic feedback to represent abstract concepts in science has shown mixed results in terms of their effect on students' conceptual learning [59]. While Wiebe et al [55], Park et al [35], and Sanchez et al [41] found that the combination of visual and haptic feedback did not provide an advantage over the visual modality, Magana et al [23] determined that adding haptic feedback in a sequenced manner increased students' performance. Therefore, we used a visuohaptic simulation following a sequenced approach and visual-only to identify students' improvements of conceptual learning and representational skills of FBDs for truss systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work that has used visual cues and haptic feedback to represent abstract concepts in science has shown mixed results in terms of their effect on students' conceptual learning [59]. While Wiebe et al [55], Park et al [35], and Sanchez et al [41] found that the combination of visual and haptic feedback did not provide an advantage over the visual modality, Magana et al [23] determined that adding haptic feedback in a sequenced manner increased students' performance. Therefore, we used a visuohaptic simulation following a sequenced approach and visual-only to identify students' improvements of conceptual learning and representational skills of FBDs for truss systems.…”
Section: Discussionmentioning
confidence: 99%
“…Examples in higher education investigating the value of adding haptic feedback to virtual environments are found in Park et al [35] for electrical charges (n = 38) and Sanchez et al [41] for electricity and magnetism (n = 66). At the postgraduate education level, Schönborn et al [44] performed a study with 20 students who learned about protein-ligand interactions, and they found that students in the control condition performed twice the number of actions to obtain a less relevant result than the students in the haptic group.…”
Section: Introductionmentioning
confidence: 99%
“…Computer applications and systems have experienced exponential growth in the creation of simulators and learning stations, and nowadays they are a feasible and novel solution to improve learning and training [22]. The current trend focuses on the addition of haptic devices to simulators to provide force feedback [12][13][14]. In the area of Electricity and Magnetism, virtual simulators have also been studied in recent years.…”
Section: Related Workmentioning
confidence: 99%
“…Recent visuo-haptic simulators for Electricity and Magnetism have concentrated on helping students to determine the direction of the electric/magnetic forces to infer the corresponding geometry of the electric/magnetic fields [14]. Sanchez et al created a haptic simulation to teach freshmen engineering students about electromagnetism [12]. The aim of their study was to examine the efficacy of these simulations in the students' learning process.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation